Association between dopamine genes, adiposity, food addiction, and eating behavior in Chilean adult - Luengo, Nicole; Goldfield, Gary S.; Obregón, Ana M. (Frontiers in Nutrition, 2024)
A frequent consumption of high sugar/fat foods can affect dopamine signaling in the brain and cause sustained stimulation of the reward system. It has been hypothesized that a hypodopaminergic trait results in an individual overeating in order to increase brain DA. Genetic variants in this route have been connected with addiction and eating behaviors. Most studies focus on a specific SNP, and few studies have used multilocus genetic scores, which quantify genetic risk on a continuum. Aim: to assess the relationship between multilocus genetic scores based on multiple gene variants in the dopaminergic pathway and measurements of anthropometry, eating behavior, food reinforcement, and food addiction (FA) in Chilean adults.We recruited 221 Chilean adults for a cross-sectional study. A standard anthropometric measurement procedure was followed and eating behavior was examined using the Three Factor Eating questionnaire (TFEQ), Food Reinforcement Value Questionnaire (FRVQ), Yale Food Addiction Scale (YFAS) and 24-h diet recall. Multilocus genetic scores were calculated using TaqMan assays (rs1800497-rs1799732-rs6277-rs4680).Results: No differences were found in the entire sample for anthropometric measurements, by MLGS. We found that participants with a score ³ 2.0 in the MLGS showed higher food choices on the RVFQ and lower energy intake in protein, lipids, SAFA, MUFA, PUFA, dietary cholesterol, omega-3 and Omega-6 fatty acids in the 24-h recall (p< 0.05). Stratified by nutritional condition, the group with obesity had inferior scores on cognitive restriction, greater scores on uncontrolled eating, emotional eating, and responding to palatable food in the RVFQ. Also, in subjects with obesity, there was more food addiction in the group scoring "MLGS ³ 2.0 or low dopamine signaling" (53%), compared to the group scored "MLGS < 2.0 or high dopamine signaling" (23%) (p-value; 0.05). Emotional Eating scores correlated positively with MLGS in subjects with obesity.In adults with obesity, the MLGS of the dopamine pathway, reflecting hypodopaminergic signaling, was associated with greater scores on food addiction and altered eating behavior traits.